2008
DOI: 10.1016/j.chroma.2008.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of different bioactive compounds in functional drinks by high-performance liquid chromatography

Abstract: 12In the present work, an HPLC method is proposed to simultaneously detect and quantify 13 water and fat soluble vitamins, phenolic compounds, carotenoids and chlorophylls in a 14 single run, by using an ultradeactivated C18 column and gradient separation using 15 trifluoroacetic acid, water and methanol. It is shown that the HPLC method provides 16 baseline separation of all these compounds with good resolution values in 40 min. 17Moreover, other figures of merit of the method show a good linear response and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The color intensity of the honey samples ranged from 254 to 2034 mAU (Table 2), which is comparable to those reported by other authors [5,6,27,28]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The color intensity of the honey samples ranged from 254 to 2034 mAU (Table 2), which is comparable to those reported by other authors [5,6,27,28]. …”
Section: Resultssupporting
confidence: 88%
“…ABS 450 was used because it has previously been reported that anthocyanins, a class of flavonoids present in functional drinks [27], and carotenoids have absorption maxima at 450 nm. In this study, we found that three dark amber samples (BDH-4, 7 and 8) also contained high levels of phenolic and flavonoid compounds.…”
Section: Resultsmentioning
confidence: 99%
“…A modified HPLC method, previously developed in CIAL laboratory (Madrid, Spain) was used (Mendiola and others ). Shortly, analytes were separated on an ACE‐100 Å C18 (150 mm × 4.6 mm, 3 μm particle size; Advanced Chromatographic Technologies, Aberdeen, U.K.) in a single run, using combined isocratic and linear gradient elution with a mobile phase consisting of 0.010% TFA (solvent A, pH 3.9) and methanol (solvent B) at the flow rate of 0.7 mL/min using an Agilent 1100 HPLC apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…The most suitable detection wavelength for simultaneous vitamin‐polyphenol determination was 280 nm. Quantification of the different families of compounds was performed by building a calibration curve for each of them, as described by Mendiola and others ().…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that carotenoid distribution in citrus is extremely complex, with the largest number of carotenoids founded in any fruit (Meléndez-Martínez, Vicario, & Heredia, 2003). Fruit juices, drinks and mixed beverages have widely different carotenoid content, which mainly depend on the ingredients of the samples under study (Mendiola et al, 2008;. b-Carotene normally constitutes between 25% and 30% of total carotenoids in fruits (Bitton & Hornero-Méndez, 2001); however, unripe fruits usually show high contents of lutein (Gross, 1987).…”
Section: Phenolic and Carotenoid Profilementioning
confidence: 99%